IMPLEMENTATION OF THE INDEX CARD MATCH LEARNING MODEL TO IMPROVE SOCIAL STUDENTS LEARNING OUTCOMESAT GRADE V STUDENTS OF STATE ELEMENTARY SCHOOL 5 B SRIKATON - Shintya Shintya (CV Grasta Glory, 2026)
This study aims to determine whether the Index Card Match learning model can improve the learning outcomes of fifth grade elementary school students in Integrated Science (IPS). The research was conducted at SD Negeri 5 B Srikaton, musirawas District. This research is a classroom action research (PTK), with the research subjects being 20 fifth-grade students, consisting of 11 boys and 9 gils. The model used is the Index Card Match learning model, and the data collection techniques are quantitative and qualitative. The research consists of your stages: planning, implementation, observation, and reflection. The results of this study indicate and improvement in IPAS learning outcomes for fifth-grade students at SD Negeri 5 B Srikaton using the Index Card Match learning model. In cycle 1, students achieveda mastery learning score was 85%. Based on the research findings, it is concluded that the Index Card Match learning model can improve (IPS) learning outcomes in elementary schools.